Attending at a Low Intensity Increases Impulsivity in an Auditory Sustained Attention to Response Task. (December 2015) - Roebuck, Hettie; Guo, Kun; Bourke, Patrick
Why attention lapses during prolonged tasks is debated, specifically whether errors are a consequence of under-arousal or exerted effort. To explore this, we investigated whether increased impulsivity is associated with effortful processing by modifying the demand of a task by presenting it at a quiet intensity. Here, we consider whether attending at low but detectable levels affects impulsivity in a population with intact hearing. A modification of the Sustained Attention to Response Task was used with auditory stimuli at two levels: the participants' personal "lowest detectable" level and a "normal speaking" level. At the quiet intensity, we found that more impulsive responses were made compared with listening at a normal speaking level. These errors were not due to a failure in discrimination. The findings suggest an increase in processing time for auditory stimuli at low levels that exceeds the time needed to interrupt a planned habitual motor response. This leads to a more impulsive and erroneous response style. These findings have important implications for understanding the nature of impulsivity in relation to effortful processing. They may explain why a high proportion of individuals with hearing loss are also diagnosed with Attention Deficit Hyperactivity Disorder.